Efficacy of SmartLossSM, a smartphone‐based weight loss intervention: Results from a randomized controlled trial. (May 2015) - Martin, Corby K.; Miller, Anastasia C.; Thomas, Diana M.; Champagne, Catherine M.; Han, Hongmei; Church, Timothy
<x xml:space="preserve">Abstract</x> Objective Test the efficacy of SmartLossSM, a smartphone‐based weight loss intervention, in a pilot study. Design and Methods A 12‐week randomized controlled trial. Adults (25 ≤ BMI ≤ 35 kg/m2) were randomized to SmartLoss (n = 20) or an attention‐matched Health Education control group (n = 20). SmartLoss participants were prescribed a 1, 200 to 1, 400 kcal/d diet and were provided with a smartphone, body weight scale, and accelerometer that wirelessly transmitted body weight and step data to a website. In the SmartLoss Group, mathematical models were used to quantify dietary adherence based on body weight and counselors remotely delivered treatment recommendations based on these objective data. The Health Education group received health tips via smartphone. A mixed model determined if change in weight and other endpoints differed between the groups (baseline was a covariate). Results The sample was 82.5% female. Mean ± SD baseline age, weight (kg), and BMI were 44.4 ± 11.8 years, 80.3 ± 11.5 kg, and 29.8 ± 2.9 kg/m2, respectively. One participant was lost to follow‐up in each group before week 4. Weight loss was significantly (P < 0.001) larger in the SmartLoss (least squares mean ± SEM: −9.4 ± 0.5%) compared with the Health Education group (−0.6 ± 0.5%). Conclusions SmartLoss efficaciously promote clinically meaningful weight loss compared with an attention‐matched control group. Smartphone‐based interventions might prove useful in intervention dissemination.